Asymmetric synthesis of (+)-lentiginosine using a chiral aziridine based approach - Yoon, Hojong; Cho, Kyung Seon; Sim, Taebo (PERGAMON-ELSEVIER SCIENCE LTD, 2014)
The synthesis of the indolizidine alkaloid, (+)-lentiginosine, is described. A key feature of the preparative route is the efficient and stereoselective construction of a dihydroxylated pyrrolidine via Sharpless asymmetric dihydroxylation of an aziridine-enoate, which was prepared from commercially available 1-(S)-alpha-methylbenzylaziridine-2-methanol. In addition, a regioselective aziridine-to-pyrrolidinone ring expansion process followed by a Wittig olefination was employed to construct a late stage pyrrolidine intermediate that was transformed into (+)-lentiginosine. (c) 2014 Elsevier Ltd. All rights reserved.
Keywords: CONCISE TOTAL-SYNTHESIS; DIRECTED DIHYDROXYLATION; STEREOSELECTIVE-SYNTHESIS; ALLYLIC ALCOHOLS; POLYHYDROXYLATED ALKALOIDS; ABSOLUTE-CONFIGURATION; LENTIGINOSINE; INHIBITORS; TRICHLOROACETAMIDES; (-)-LENTIGINOSINE